2013
DOI: 10.1111/glob.12010
|View full text |Cite
|
Sign up to set email alerts
|

Gender, labour and the law: the nexus of domestic work, human trafficking and the informal economy in the United Arab Emirates

Abstract: Based on ethnographic fieldwork with female migrants in the United ArabEmirates, the focus of this article is on the confluence of human trafficking discourses, gendered migration, domestic work and sex work in the UAE. I explore three main findings. First, domestic work and sex work are not mutually exclusive. Second, women choose to enter sex work in preference to domestic work because of poor working conditions in the latter. Third, global policies on human trafficking that seek to restrict female migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 17 publications
1
25
0
2
Order By: Relevance
“…Our fieldwork has shown that the informal waste pickers are not passive underdogs, but that they have developed strategies to improve their economic activity. The choice to work in the informal economy might actually be an empowered choice rather than the result of sheer necessity to work informally due to a lack of formal employment opportunities, as has been demonstrated for other parts of the informal economy (De Soto, 1989;Mahdavi, 2013). However, especially the case of Accra has shown that for some informal workers, waste picking is still a last and only resort.…”
Section: Waste Pickers In the Globalmentioning
confidence: 96%
See 1 more Smart Citation
“…Our fieldwork has shown that the informal waste pickers are not passive underdogs, but that they have developed strategies to improve their economic activity. The choice to work in the informal economy might actually be an empowered choice rather than the result of sheer necessity to work informally due to a lack of formal employment opportunities, as has been demonstrated for other parts of the informal economy (De Soto, 1989;Mahdavi, 2013). However, especially the case of Accra has shown that for some informal workers, waste picking is still a last and only resort.…”
Section: Waste Pickers In the Globalmentioning
confidence: 96%
“…relates to gross domestic product (GDP) and employment. At micro-level many single case studies on specific examples of informal economy have been conducted (for instance, Boels, 2014;Mahdavi, 2013;Thieme, 2015), but the attempts to compare several case studies are rare. This article contributes to the growing body of studies on micro-characteristics of informal work, developing a dialogue between two case studies on waste pickers' activities in two different cities (Accra and Porto Alegre).…”
Section: Waste Pickers In Accra (Ghana)mentioning
confidence: 99%
“…A common observation made by scholars on female migration in South-East Asia and elsewhere is that women encounter a broader range of social and bureaucratic negotiations, and higher moral expectations for their migratory success and return, as compared to their male peers [6][7][8][9][10][11][12][13][14][15][23][24][25][26][27][28][32][33][34][35][36][37]51,52,[56][57][58][59][60][61][62][63][64][65]. Following these scholars, this article highlights the ways that representations of Indonesian migrants as heroes of development, or exploited victims, commonly share local culturally and religiously inflected assumptions about gender and morality.…”
Section: Theoretical Framework: Labor Migration Gender and Developmentmentioning
confidence: 99%
“…In Section 4, I demonstrate how the gendered and moral assumptions embedded in public representations of migrants as heroes of development are similarly evoked in Indonesian media accounts of female migrants as victims of abuse and exploitation. Further, I complicate the hero-victim dichotomy by considering the category of the "immoral victim", a category more familiar to and discussed in relation to media representations of migrants in countries where they work, such as Saudi Arabia [35], Hong Kong [32] and Singapore [36,37]. I then conclude with a discussion on the contribution of this article: an analysis of how gendered moral hierarchies embedded in these representations of migrants' success or victimhood potentially legitimize extreme violence against "immoral" migrants as deserved.…”
Section: Introductionmentioning
confidence: 99%
“…La bibliografía existente sobre esta dicotomía héroe-víctima se basa en gran medida en trabajadores migrantes de Indonesia (Ford 2002 (Ladegaard 2013;Mahdavi 2013; Yeoh y Huang 2010). Sin embargo, mi argumento es que el enfoque del Estado indonesio sobre la moral y la responsabilidad individual de los migrantes es una estrategia que concibe la migración como un camino hacia el desarrollo, haciendo que la explotación laboral aparezca como un efecto secundario inevitable.…”
Section: Introductionunclassified